A gap in HD 92945's broad planetesimal disc revealed by ALMA. Issue 1 (7th January 2019) - Marino, S; Yelverton, B; Booth, M; Faramaz, V; Kennedy, G M; Matrà, L; Wyatt, M C
ABSTRACT: In the last few years, multiwavelength observations have revealed the ubiquity of gaps/rings in circumstellar discs. Here we report the first ALMA observations of HD 92945 at 0.86 mm, which reveal a gap at about 73 ± 3 au within a broad disc of planetesimals that extends from 50 to 140 au. We find that the gap is 20^+10_-8 au wide. If cleared by a planet in situ, this planet must be less massive than 0.6 M Jup, or even lower if the gap was cleared by a planet that formed early in the protoplanetary disc and prevented planetesimal formation at that radius. By comparing opposite sides of the disc, we also find that the disc could be asymmetric. Motivated by the asymmetry and the fact that planets might be more frequent closer to the star in exoplanetary systems, we show that the gap and asymmetry could be produced by two planets interior to the disc through secular resonances. These planets excite the eccentricity of bodies at specific disc locations, opening radial gaps in the planetesimal distribution. New observations are necessary to confirm if the disc is truly asymmetric, thus favouring the secular resonance model, or if the apparent asymmetry is due to a background galaxy, favouring the in situ planet scenario. Finally, we also report the non-detection of CO and HCN gas, confirming that no primordial gas is present. The CO and HCN non-detections are consistent with the destruction of volatile-rich Solar system-like comets.